COVID-19 and the nutrition of children and adolescents - Mikulec, Anna; Zborowski, Marek; Cisoń-Apansewicz, Urszula; Kowalski, Stanisław (Journal of Education, Health and Sport, 2023)
Introduction During childhood and adolescence, a properly balanced diet is very important, as it has a direct impact on health. During the COVID-19 pandemic, care for the proper diet has become particularly important, especially due to the growing wave of overweight and obesity among children and adolescents, observed especially in adolescence. Aim The aim of the study was to determine the impact of the COVID-19 pandemic on the nutrition of children and adolescents. Material and methods The research tool was a questionnaire consisting of questions mainly related to the nutrition of children and adolescents. Adolescents are only included if they and their parents or legal guardians have given their informed consent to participate. If they expressed their willingness to participate in the study, the students received an electronic link to the questionnaire. Results Most of the respondents were girls / women living in the countryside. The impact of the COVID-19 pandemic on eating behavior was observed in 61% of respondents. Social isolation in 61% of people did not affect the regularity of eating meals. Most of the respondents (54%) did not observe an increase in their appetite during the lockdowns. The number of people consuming 1 and 5 meals has increased, and the number of people consuming 2 and 3 meals a day has decreased. Conclusions The time of social isolation associated with the COVID-19 pandemic has affected the nutrition of children and adolescents. The number of people eating 1 and 5 meals during social isolation has increased, and the number of people eating 2 and 3 meals has decreased. During social isolation, a decrease in the physical activity of children and adolescents was observed.